IN VITRO CYTOTOXIC STUDY OF GREEN SYNTHESIZED GOLD AND SILVER NANOPARTICLES USING ECLIPTA PROSTRATA (L.) AGAINST HT-29 CELL LINE - Rajasekar, Arvindganth; Janakiraman, Vardhana; Govindarajan, Kathiravan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The objective of this study is to synthesize gold and silver nanoparticles using the extracts of Eclipta prostrata. Methods: The nanoparticles synthesize is carried out using the powdered leaves and mixed with distilled water. The filtered extract was then mixed with aqueous solution of HAuCl4 (1 mM) and AgNo3 (1 mM), and the reaction volume was made up to 100 ml. Then, the characterization of nanoparticles was carried out using ultraviolet, infrared, scanning electron microscope, and the cytotoxic activity of the nanoparticles were investigated against HT- 29 cancer cell lines. Results: From the study, it was found that the plant extract was able to synthesize nanoparticles, and the synthesized nanoparticles were found to be toxic against the cancer cell line HT-29. Conclusion: In the present study, both silver and gold nanoparticles were synthesized using the plant extract of E. prostrata. The synthesized nanoparticles were found to be effective against HT 29 cancer cells. The green synthesized nanoparticles were found to be cost-effective, simpler and environmentally safe. As the nanotechnology is an emerging field in medicine, the biological synthesis of nanoparticles helps in the other way. From the present study, the nanoparticles synthesized were thus proved against various studies novely. Hope this paves way for the better development of nanoparticle production in the large scale amount. Keywords: Nanoparticles, Eclipta prostrata, Scanning electron microscope, HT-29 cell line. Â§Both authors are equally contributed